Ангелы смерти. Женщины-снайперы, 1941-1945 - Бегунова Алла Игоревна (Военные тайны XX века, 2014)
Экземпляры: ф9, ф10 (201506) / Инвентарный номер: 51217 / Цена: 193.16 / Сис.шифр: 63.3(2)622 / Авт.знак: Б 37 / ГРНТИ: 03 / ББК: 63.3(2)622